Differential Sexual Maturity Among Breeding Adults of Black Sea Turtle (Chelonia mydas agassizii) from Michoacan, Mexico - Carlos Delgado-Trejo; Miguel Ángel Reyes-López; David Guillermo Pérez-Ishiwara; Omar Domínguez-Domínguez; Andrea Tapia-García; Fátima Yedith Camacho-Sánchez; Cutzi Bedolla-Ochoa (Diversity)
This work assessed the sexual maturity of breeding females and males of black sea turtles (Chelonia mydas agassizii) from the population in Michoacan, Mexico. This study also provides the first report of the age at sexual maturity for male black sea turtles in the eastern Pacific. Using information on juvenile growth rate, length, and age at recruitment of juveniles in the developmental habitats in Baja California (Magdalena Bay), sexual maturity was estimated from the minimum and average standard carapace lengths (SCL) of nesting females (n = 1500) on Colola Beach and males (n = 132) captured at sea using the “swim up” technique. Differential sexual maturity was found in females and males. The minimum age at sexual maturity for males was 23.0 years at a minimum size of 61.1 cm SCL and the maximum age at sexual maturity was 32.5 years at a maximum size of 76.6 cm SCL. The minimum age of sexual maturity for nesting females was 24.9 years at a minimum size of 64.2 cm SCL, while the age of sexual maturity for maximum size was 42.9 years at a 93.4 cm SCL. Differences in the age at sexual maturity influence reproductive behavior and female carapace shape, impacting mating success.